The Branding Strategy of the "Shobat" Program as a Differentiator for Integrated Islamic Schools: A Case Study of Islamic Junior Highschool - Muhammad Thorif Abdurrofi; Mohamad Joko Susilo (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2026)
Integrated Islamic education branding has become an essential strategy for enhancing the competitiveness of educational institutions amid growing competition. This study examines the branding strategy of the SHOBAT program (Sholih dan Berprestasi Terpadu) in shaping the institutional image of an Islamic Junior Highschool in Yogyakarta as a leading Islamic school. A qualitative descriptive approach was utilized, involving data collection through interviews with nine informants, observations, and documentation. The findings reveal that the branding strategy was implemented across three main dimensions: internal branding, focused on internalizing Islamic values and enhancing teacher competence; external branding, through digital media and strategic partnerships; and reinforcing the SHOBAT program, which integrates piety, academic excellence, and 21st-century skills. This approach has led to increased public trust, stakeholder loyalty, and greater appeal to prospective students. The research contributes to the theoretical development of branding in integrated Islamic education and provides practical insights for other Islamic schools aiming to differentiate themselves through distinctive programs.